A Comparative study of COVID-19 related internalized stigma, Anxiety and Depressive symptoms among COVID-19 Cases and Suspects in Nepal (Journal of Psychiatrists' Association of Nepal, 2025)
Background: The COVID-19 pandemic has been associated with significant social and internalized stigma, particularly in low-resource settings. Yet, few studies have examined its psychological impact. This study aims to (1) find out the levels of COVID-19-related internalized stigma among confirmed COVID-19 cases and suspects in Nepal, (2) compare their scores and scores of anxiety and depressive symptoms between the two groups, and (3) find the associations of scores anxiety, and depressive symptoms with COVID-19-related internalized stigma in both groups.Methods: It was a cross-sectional study conducted during the first wave (July–November 2020) in five health facilities in two provinces of Nepal,  with 306 COVID-19 cases and 89 suspects. A semi-structured questionnaire, adapted Internalized Stigma of Mental Illness scale, and Hospital Anxiety and Depression Scale were administered. Descriptive and correlation analyses were used to compare the two groups.Results: COVID-19 cases reported significantly more high COVID-19-related internalized stigma (25.2% cases, 3.4% suspects) (p